From soil to plant: strengthening carrot defenses against Meloidogyne incognita with vermicompost and arbuscular mycorrhizal fungi biofertilizers - Ahamad, Lukman; Bhat, Aashaq Hussain; Kumar, Harendra; Rana, Aasha; Hasan, Md. Nurul; Ahmed, Ishtiaq; Ahmed, Shakoor; Machado, Ricardo A. R.; Ameen, Fuad (Frontiers in Microbiology, 2023)
Sustainable agricultural practices for controlling crop pests are urgently needed to reduce the reliance on chemical pesticides, which have long-term detrimental effects on ecosystems. In this study, we assessed the effectiveness of arbuscular mycorrhizal fungi (AMF) and vermicompost (Vc) supplementation, alone and in combination, in mitigating the negative impacts of Meloidogyne incognita infestation on carrot (Daucus carota L.) growth, development, and physiology in a greenhouse setting. Our findings revealed that M. incognita had a significant detrimental effect on plant growth, biomass accumulation, and photosynthetic pigment and carotenoid content. However, the incorporation of Vc and AMF into the soil, either individually or in combination, significantly alleviated the negative effects of nematode infestation on carrot plants. This was accompanied by an increased induction of phenolic compounds (+23.78%) and defense enzymes such as peroxidase (+15.65%) and polyphenol oxidase (+29.78%), and a reduced severity of nematode infestation on Vc and AMF-treated plants (+55.51%) compared to nematode-infested plants. These results highlight the potential of utilizing cultural practices and beneficial microorganisms for sustainable and environmentally-friendly management of agricultural pests.